Relationship between xerostomia and psychotropic drugs in patients with schizophrenia: evaluation using an oral moisture meter. (24th September 2016) - Okamoto, A.; Miyachi, H.; Tanaka, K.; Chikazu, D.; Miyaoka, H.
Summary: What is known and objective: Patients with schizophrenia are most commonly treated with antipsychotic medications, often with the addition of anxiolytics. This study used an oral moisture meter to evaluate xerostomia in patients with schizophrenia taking typical and atypical antipsychotics, anxiolytics and non‐psychotropic medications. Methods: Patients diagnosed with schizophrenia according to ICD‐10 criteria in the Department of Psychiatry, Kitasato University East, and affiliated hospitals were studied. All patients were on psychotropic medications. Patients with diseases associated with xerostomia, such as Sjögren's syndrome I, were excluded. Results and discussion: A total of 127 patients were enrolled. Mean oral moisture was 27·81 ± 2·27% (normal, ≥30·0%). A significant association was observed between objective oral moisture and the subjective sense of dry mouth. Multivariate analysis revealed a negative correlation between the number of antipsychotics and, especially, anxiolytics, and the degree of oral moisture. Drug dosages themselves were not significantly correlated with dry mouth. These findings suggest that objective oral moisture measurements show decreased moisture in patients on these medications and that the degree of moisture shows a greater negative correlation with the number, as opposed to the dosages, of psychotropic drugs administered. What is new and conclusions: When patients with schizophrenia visit a dental clinic, it is important for the dentist to accurately assess the degree of oral moisture and to determine the medications being taken. Based on these findings of the association of polypharmacy with xerostomia, dentists are encouraged to inform the psychiatrist of the need to actively manage patients' xerostomia. Abstract : Xerostomia, a sensation of dry mouth, is a common side effect of many medications used to treat schizophrenia. Our multivariate analysis revealed a negative correlation between the number of antipsychotics used, particularly anxiolytics, and the degree of oral moisture in patients with schizophrenia.